Finding aid IFPRI repository 1995-2003 - International Food Policy Research Institute (International Food Policy Research Institute, 1995)
This is an export of ebrary.ifpri.org of publications for the years 1995 to 2003. All records are migrated to CGSpace individually and this table is retained for the purpose of archival reference.